(untitled) (Innovative professional education, 2024)
The results of the analysis of the problem of the development of digital competence of future teachers of institutions of higher pedagogical education in domestic and scientific literature as one of the eight key competences of a modern specialist are highlighted. The results of the master’s self-assessment of the level of its formation at the time of obtaining professional education are presented, and the method of calculating the results is described. The least developed indicators in the composition of digital competences are singled out: training of education seekers and evaluation of its results; use and analysis of digital resources in the educational process; development of digital competence and ability for professional development. Factors influencing the development of digital competence of future teachers and the basis of professional success are determined.